EXERCISE BEHAVIORS AND BARRIERS OF STUDENTS IN SAMUTSAKORN TECHNICAL COLLEGE - Buaphet, Chairit; Tengku Sulaiman, Raja Syed; Choeychom , Kongkiat (Academic Journal of Thailand National Sports University, 2020)
The purpose of this research was to study the behaviors in and the barriers to exercise in Samutsakorn Technical College students. The samples of this study consisted of 362 students who were acquired by cluster random sampling. The instrument used to collect the data are questionnaires consisting of checklist, 5-point Likert-type scale, and open ended questions. For this research, a total IOC index of content validity was ranged at 0.73. While a whole reliability of the questionnaire determined by cronbachs alpha coefficient was 0.84. The statistics for the data analysis were frequency and percentage. Based on the analysis of the gathered data, the two findings were: 1) Samutsakorn Technical College students usually exercised alone on Sunday, 16.00 hrs. to 18.00 hrs. The main purpose of exercising was to maintain their health. The public parks were the place for exercise of the students. This was because it was close to their residence. Before exercise most of students did warm up for 5-10 minutes and cool down by stretching exercise 5–10 minutes per each time. Cardiovascular efficiency development with walking exercise was taken 30 minutes per each time. Strength exercise with weight training equipment was sometimes practiced 1–2 days a week. Flexibility exercise was regularly practiced 1–2 days a week, and duration of the exercise was less than 20 minutes and 2) there were four important barriers to exercise in Samutsakorn Technical College students, namely weather condition, lack of knowledge and understanding about exercise, no time to exercise because of a busy schedule and physical condition.